Sorcery and witchcraft beliefs on the front line of public health response in Papua New Guinea and beyond - Forsyth, Miranda; Taylor, Joanne; Housen, Tambri; Marsh, Celeste; Gibbs, Philip; Kipongi, William (Western Pacific Surveillance and Response, 2024)
Problem: Many communities refer to sorcery or witchcraft to explain misfortunes such as sickness, death and disability. The effects of these beliefs on public health service delivery have long been overlooked. Beliefs in sorcery and witchcraft are significant challenges for health-care workers to understand to deliver better health outcomes and avoid inadvertently triggering accusations of witchcraft that may lead to violence.Context: This paper examines the impacts of accusations of sorcery and related violence on the provision of health care in Papua New Guinea.Action: The discussion focuses on a workshop held in Papua New Guinea in September 2022 with health extension officers on the topic of health-care delivery and sorcery accusations.Lessons learned: The workshop confirmed the challenges that beliefs in sorcery and witchcraft present for health extension officers and suggested several strategies that could be used to navigate them. It identified several possible future measures that those on the front line of community health-care delivery considered most important in responding to the issue. These included educating health-care workers on how to effectively address sorcery beliefs when delivering health care and developing communication techniques on the causes of death and sickness that avoid triggering sorcery accusations.Discussion: This paper reviews the findings of the workshop in the broader context of the effects of beliefs in witchcraft on public health delivery globally. Because of the close connections between sorcery beliefs and health, equipping health-care workers and field epidemiologists with strategies to address these beliefs effectively is critical to delivering better health care, facilitating timely response to public health events, and helping to prevent violence related to sorcery accusations. This need exists in all countries where sorcery beliefs related to health, illness, disability and death are prevalent.
Keywords: witchcraft; magic; epidemiology